2000
DOI: 10.1159/000018366
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Topical Administration of a Petrolatum Formulation by a Novel Disposable Diaper

Abstract: Background: Diaper dermatitis is a common childhood affliction. Aiming to help reduce the prevalence of this problem, we have developed a novel diaper to deliver to the skin dermatological formulations intended to help protect the skin from overhydration and irritation. Objective: To determine the clinical benefits of a novel disposable diaper designed to deliver a petrolatum-based formulation continuously to the skin during use. Methods: Two independent, blinded, randomized clinical trials were conducted, inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
68
0
11

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 6 publications
(7 reference statements)
0
68
0
11
Order By: Relevance
“…It has been shown that infants in superabsorbent diapers had significantly less diaper dermatitis than those in conventional disposable and cloth diapers [20, 21]. Moreover, a novel diaper has been developed with continuous topical administration of a petrolatum formulation which is described to reduce the contact irritation problems associated with diaper use [22]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that infants in superabsorbent diapers had significantly less diaper dermatitis than those in conventional disposable and cloth diapers [20, 21]. Moreover, a novel diaper has been developed with continuous topical administration of a petrolatum formulation which is described to reduce the contact irritation problems associated with diaper use [22]. …”
Section: Discussionmentioning
confidence: 99%
“…Esto pone de manifiesto que el uso de pañales desechables no sólo es eficaz, sino también seguro y que, en términos generales, los pañales con materiales absorbentes se asocian con formas clínicas menos graves de dermatitis por pañal que los pañales convencionales y los pañales de tela; 12,14,15 por último, que los cuidadores son capaces de reconocer estas ventajas.…”
Section: Discussionunclassified
“…En general, existen estudios [12][13][14][15][16]18 sobre la eficacia de los pañales para la prevención de dermatitis por pañal, incluso evaluada mediante revisión sistemática, 27 que ponen de manifiesto que los pañales con centro de celulosa son superiores a los de tela; los pañales con materiales absorbentes en gel son superiores a los pañales con centro de celulosa exclusivamente, y que los pañales con liberación de formulaciones por contacto son superiores a aquéllos que no las liberan. El pañal BBTips ® evaluado en el presente estudio pertenece al grupo de liberación por contacto y, a pesar de ser semejante a Huggies UltraConfort ® por pertenecer al grupo de absorbentes con gel, la superioridad global de BBTips ® puede estar en relación con esta diferencia.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Vaseline known being with moisturising as well as water impermeability properties protect the skin [5,10]. In one study, 0 -18 month old children with diaper dermatit were also treated with zinc oxide/vaseline containing diaper as decreased the ratio and severity of diaper dermatit [19,24,25]. In other study diaper containing vaseline was seen to reduce the severity and redness in the 0 -18 month old children with diaper dermatit [20].…”
Section: Discussionmentioning
confidence: 99%